The Economic Impact of Psychological Distress in the Australian Coal Mining Industry. Issue 5 (May 2016) - Ling, Rod; Kelly, Brian; Considine, Robyn; Tynan, Ross; Searles, Andrew; Doran, Christopher M.
Abstract : Objective: The aim of this study was to estimate the economic impact of psychological distress among employees of the Australian Coal Mining Industry. Methods: Sample data were gathered from 1456 coal mining staff across eight sites in two Australian states. Two measures were taken of work time lost over four weeks due to psychological distress: (1) full-day absences; (2) presenteeism. Lost work time was valued using hourly wages. Sample data was modeled to estimate annual monetary losses for the Australian Coal Mining Industry. Results: For the sample, estimated annual value of time lost due to psychological distress was $4.9 million ($AUS2015) ($0.61 million per mine), and for the Australian Coal Mining Industry, $153.8 million ($AUS2015). Conclusion: Psychological distress is a significant cost for the Australian Coal Mining Industry. Relevant intervention programs are potentially cost-effective.